2019
DOI: 10.1186/s12917-019-1958-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of chicken egg yolk immunoglobulins (IgY) against enterotoxigenic Escherichia coli K88 adhesion in weaned piglets

Abstract: Background Enterotoxigenic Escherichia coli K88 ( E. coli K88) are considered as a major cause of diarrhea and death in newly weaned piglets. Oral passive immunization with chicken egg yolk immunoglobulins (IgY) have attracted considerable attention for treatment of gastrointestinal infection due to its high specificity. In this study it was estimated the protective effect of anti-K88 fimbriae IgY against E. coli K88 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…The body weight, feed intake, and fecal score were detected weekly, and the feed conversation ratio was calculated. The fecal consistency score was assessed by a modified method according to our previous study (Wang et al, 2019): 1 = solid, 2 = pasty, and 3 = liquid. The piglets were sacrificed on day 21 to collect blood, liver tissue, intestinal tissue (including duodenum, jejunum, ileum, and colon), and digesta of cecum and colon.…”
Section: Animals and Experiments Designmentioning
confidence: 99%
“…The body weight, feed intake, and fecal score were detected weekly, and the feed conversation ratio was calculated. The fecal consistency score was assessed by a modified method according to our previous study (Wang et al, 2019): 1 = solid, 2 = pasty, and 3 = liquid. The piglets were sacrificed on day 21 to collect blood, liver tissue, intestinal tissue (including duodenum, jejunum, ileum, and colon), and digesta of cecum and colon.…”
Section: Animals and Experiments Designmentioning
confidence: 99%
“…In accordance with the current study, previous studies reported that the use of IgY could reduce the incidence of diarrhea of weaned piglets challenged with toxicogenic E. coli [ 11 , 26 , 41 ]. The clinical symptoms observed for piglets suggested that IgY-treated piglets recovering from E. coli K88 induced-diarrhea was faster than piglets untreated with IgY [ 42 ]. Moreover, dietary supplementation with a mixture of plant essential oils, eucalyptus essential oil, Petroselinum crispum essential oil, and thyme essential oil had a similar anti-diarrheal effect to AGPs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the antibacterial effect of IgY may be related to its ability to prevent the adhesion of pathogenic bacteria in the intestine [ 9 , 12 ]. IgY was found to significantly block E. coli K88 to bind to porcine small intestinal mucus [ 42 ]. This blocking was effective because IgY can bind to the components exposed on the surface of E. coli K88 resulting in structural alterations, which might impede its adhesion to intestine [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, feeding DEP significantly reduced the mucosal concentration of pro-inflammatory IL-1β compared to CON. The IgY in DEP can block the adhesion of pathogens to the epithelial lining, preventing or reducing the need for an inflammatory response and overproduction of IL-1β ( Wang et al, 2019 ). The mucosal concentration of pro-inflammatory IL-18 was increased by CON when AB+ diets were fed, but the concentration was not affected by the other diets.…”
Section: Discussionmentioning
confidence: 99%